Philosophy as the basis for the civilization development of society - Akhmet Shimshek, Haсi (Karagandy University of the name of academician E.A. Buketov, 2023)
The work deals with the relationship between civilization and philosophy, defining the relationship and features of culture and philosophy, culture and civilization. The concepts of a civilized person, personality, and social identity are comparatively analyzed, and the place of philosophy in the formation of a civilized society is defined. Man is the creator of the world. Through its actions over the centuries, it has shaped, changed and transformed the world. The material and spiritual wealth he discovered became a heritage that was collected under the name of “civilization” and passed down from generation to generation. The guardian of this heritage is philosophy. Philosophy took the leading role in the understanding of the human world, under its guidance civilizations developed and continued from generation to generation. In the same way, civilizations contributed to the development of philosophical thought through their accumulation. Great civilizations are based on the fundamental principles of their philosophy. The influence of these three elements, human, social and environmental factors, is very important in the emergence of philosophy as a science. In the concept of civilization lies the material and spiritual accumulation of society; culture, art and literature are mainly products of philosophy. There is a distinct structure between these two concepts in this context. Any civilization is based on these values.